APLIKASI FISIKA NUKLIR PADA POSITRON EMISSION TOPOGRAPHY DALAM DIAGNOSIS MEDIS - Rezki, Nazhifah; Ulfayani, Adilah; Ramadhani, Aisyah; Syam, Muthmainnah; Fadhillah, Izzatul; Nurhayati, Nurhayati; Ansar, Asnaeni (Pinisi: Physics Journal, 2025)
Nuclear physics is the study of atomic nuclei and the particles and phenomena associated with them. It plays a vital role in technology, particularly in the medical field. One medical device that applies the principles of nuclear physics is Positron Emission Tomography (PET), an imaging technology used effectively for diagnosing various diseases. The purpose of this article is to examine the use of nuclear physics in PET for medical diagnosis, including a review of the nuclear-physics mechanisms behind PET itself. This article highlights the importance of a thorough understanding of nuclear physics in medical diagnostics.